Courts of First Instance in Criminal Cases of the Republic of Azerbaijan: Jurisdiction and Simplified Procedure - Solodkova, Vasilina; Gilmanov, Idris; Gilmanov, Muhamat (Journal of History Culture and Art Research, 2018)
The UN by means of the international documents obliges the national legislator to pay to questions of jurisdiction special attention. The specified duties are concretized in paragraph 1 of article 14 of the Covenant on Civil and Political rights and in paragraph 1 of article 6 of the Convention on protection of human rights and fundamental freedoms. Providing guarantees of the rights for fair public consideration of the case by competent court without tightening is imputed an obligation of the states. Questions of jurisdiction, i.e. competence, courts on criminal cases in the territory of the Russian Federation are regulated by article 31 of the Code of Criminal Procedure of the Russian Federation. Rules of this article have the big importance. The close attention is given to questions of competence of the courts of the first instance also by the legislator of the Azerbaijan Republic. The legal system of this country enters into the Romano-German legal family, but with distinctive features. In our opinion, for simplification of office loading of courts of the first instance it is necessary to enter offenses into article 15 of the Criminal code of RA as an independent type of punishment. Besides, with the same purpose it is necessary to provide the simplified (total) procedure which is not, unfortunately, in the present legislation in the Code of Criminal Procedure of RA.